CT imaging : practical physics, artifacts, and pitfalls - Mamourian, Alexander C.; Litt, Harold I. (Oxford University Press, 2013)
CT imaging has become a mainstay of medical imaging. After 30 years this is a mature technology but the accumulation of innovations over the past decades have given it extraordinary capabilities and new applications continue to emerge. In this book Alex Mamourian uses early CT technology to explain the fundamentals of CT imaging and then builds on that base to explain how innovations such as slip-ring and multidetector arrays allow for rapid, high resolution imaging. This book covers complex applications such as CT cardiac imaging and dual-source dual-energy CT scanning as well as the pitfalls.